Analisis Faktor-Faktor Kecurangan Mahasiswa Akuntansi Pada Pembelajaran Berbasi Daring Pada Mahasiswa Akuntansi Universitas Pertiwi - Narmih Asyita; Yana Mustika; Siti Ayu Rosida (CV. Ulil Albab Corp, 2024)
This study aims to analyze the factors of cheating of accounting students in online learning case studies on accounting students at Pertiwi University. The theoretical approach used is the Fraud Pentagon theory, which is an approach to fraud factors from the elements of pressure, opportunity, rationalization, competence, and arrogance. This study uses a quantitative method. The data used is primary data obtained through questionnaires. The population of this study is all students majoring in accounting at Pertiwi University. The sample in this study is 60 students majoring in accounting at Pertiwi University. The method used in this study is the census method or total sampling using a multiple linear regression model. The results of this study simultaneously show that the pentagon's cheating theory affects academic cheating behavior. This partly suggests that pressure, opportunity, rationalization, and arrogance influence academic cheating behavior. On the other hand, opportunity has no effect on academic cheating behavior in accounting students at Pertiwi University.